Selective Enhancement of Insulin Sensitivity in the Endothelium In Vivo Reveals a Novel Proatherosclerotic Signaling Loop. Issue 5 (3rd March 2017) - Viswambharan, Hema; Yuldasheva, Nadira Y.; Sengupta, Anshuman; Imrie, Helen; Gage, Matthew C.; Haywood, Natalie; Walker, Andrew M.N.; Skromna, Anna; Makova, Natallia; Galloway, Stacey; Shah, Pooja; Sukumar, Piruthivi; et al.
Abstract : Rationale: : In the endothelium, insulin stimulates endothelial NO synthase (eNOS) to generate the antiatherosclerotic signaling radical NO. Insulin-resistant type 2 diabetes mellitus is associated with reduced NO availability and accelerated atherosclerosis. The effect of enhancing endothelial insulin sensitivity on NO availability is unclear. Objective: : To answer this question, we generated a mouse with endothelial cell (EC)–specific overexpression of the human insulin receptor (hIRECO) using the Tie2 promoter–enhancer. Methods and Results: : hIRECO demonstrated significant endothelial dysfunction measured by blunted endothelium-dependent vasorelaxation to acetylcholine, which was normalized by a specific Nox2 NADPH oxidase inhibitor. Insulin-stimulated phosphorylation of protein kinase B was increased in hIRECO EC as was Nox2 NADPH oxidase–dependent generation of superoxide, whereas insulin-stimulated and shear stress–stimulated eNOS activations were blunted. Phosphorylation at the inhibitory residue Y657 of eNOS and expression of proline-rich tyrosine kinase 2 that phosphorylates this residue were significantly higher in hIRECO EC. Inhibition of proline-rich tyrosine kinase 2 improved insulin-induced and shear stress–induced eNOS activation in hIRECO EC. Conclusions: : Enhancing insulin sensitivity specifically in EC leads to a paradoxical decline in endothelial function, mediated by increased tyrosine phosphorylation of eNOS and excess Nox2-derived superoxide. Increased EC insulin sensitivity leads to a proatherosclerotic imbalance between NO and superoxide. Inhibition of proline-rich tyrosine kinase 2 restores insulin-induced and shear stress–induced NO production. This study demonstrates for the first time that increased endothelial insulin sensitivity leads to a proatherosclerotic imbalance between NO and superoxide. Abstract : Supplemental Digital Content is available in the text.